2016
DOI: 10.1080/10253866.2016.1189417
|View full text |Cite
|
Sign up to set email alerts
|

Resolving identity ambiguity through transcending fandom

Abstract: Identity construction involves accumulating cultural, social, and symbolic capital, with initial endowments being accrued through socialization into one's habitus. This research explores the experiences of individuals that feel a lack of capital, which leads to ambiguity regarding their identities and places in the world. Through in-depth interviews, this interpretive research shows that such individuals may turn to fandom for gaining status and belonging. Fandoms are consumption fields with clear, limited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 69 publications
(108 reference statements)
1
42
1
1
Order By: Relevance
“…As any cultural formation, the fandom establishes its own rules (Schreyer, 2015) and provides their members the possibility to establish a sense of union and cohesion (Hewer, Gannon, & Cordina, 2015), as well as a model of cultural practice (Johnston, 2015). Hence, it is understood as a space where identities are built (Porat, 2010;Seregina & Schouten, 2016) and meanings are created (Jenkins, 2006).…”
Section: The Fan As a Productive Consumer In Brand Communitiesmentioning
confidence: 99%
“…As any cultural formation, the fandom establishes its own rules (Schreyer, 2015) and provides their members the possibility to establish a sense of union and cohesion (Hewer, Gannon, & Cordina, 2015), as well as a model of cultural practice (Johnston, 2015). Hence, it is understood as a space where identities are built (Porat, 2010;Seregina & Schouten, 2016) and meanings are created (Jenkins, 2006).…”
Section: The Fan As a Productive Consumer In Brand Communitiesmentioning
confidence: 99%
“…Fandom Communities (Section 6): Fandom refers to communities composed of individual fans with personal connections to various media objects (eg, television shows, movies franchises) [ 38 , 39 ]. This section asked about participation in fandom communities in online contexts.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of power relations on the development of intercultural competence requires further investigation in order to better understand inequalities in ICC. Marketing studies have shown that individuals may be conscious of and actively address power inequalities, for instance when consumers develop cultural capital even though they may initially be disadvantaged and lack such capital (Seregina and Schouten, 2017). Coskuner-Balli and Thompson (2013) show that stayat-home fathers attempt to gain cultural legitimacy through their consumption practices, highlighting the inequality between capitals, as well as how gender, race and class-related relations generate differentiations between dominant and subordinate forms of capital in a field.…”
Section: Power Negotiations Underlying Iccmentioning
confidence: 99%